Restorative Justice as an Effort to Resolve Excise Crimes Against Cigarettes - Amrullah, Rinaldy; Gustiniati, Diah; Andrisman, Tri (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
Many crime cases in Indonesian society are settled in courts, resulting in a buildup that can hinder the justice system. Meanwhile, none of the cases concerning excisable goods or cigarettes in the Free Trade Zone, which are handled by Customs and Excise in several areas, have reached the judicial process. This problem can be resolved using the restorative justice mechanism, which prioritizes the concepts of peace, mediation and reconciliation, where perpetrators, victims, law enforcement officials, and the community participate directly in the settlement of criminal cases. Therefore, the formulation of the problem in this research involved the legal position of restorative justice and its application in excise crimes. Normative juridical legal methods, supported by empirical juridical data, were used in this research. The results showed that customs and excise violations can be resolved using restorative justice without the need for a court process.